Urinary Bladder Adenocarcinoma Metastatic to the Abdominal Wall: Report of a Case with Cytohistologic Correlation - Vikas Nath; Mithra Baliga (Case Reports in Pathology)
We report a case of adenocarcinoma metastatic to the abdominal wall in a 71-year-old man with a history of primary bladder adenocarcinoma. CT-guided core biopsy was performed; imprints and histologic sections showed malignant glands lined by tumor cells with hyperchromatic nuclei and prominent nucleoli, infiltrating through skeletal muscle. Immunohistochemistry revealed positivity for CK7, membranous/cytoplasmic β-catenin, caudal-type homeobox transcription factor 2 (CDX2), and α-methylacyl coenzyme A racemase and negativity for CK20, p63, prostate-specific antigen (PSA), and prostate-specific acid phosphatase (PSAP). These findings were interpreted as metastatic adenocarcinoma, consistent with bladder primary. Primary bladder adenocarcinoma is a rare malignancy arising within glandular metaplasia and is associated with cystitis cystica and cystitis glandularis. Predisposing factors include bladder exstrophy, schistosomiasis, and other causes of chronic bladder irritation. This tumor is divided into intestinal, clear cell, and signet ring cell subtypes. Treatment involves radical cystectomy with pelvic lymph node dissection, and prognosis is unfavorable. Primary bladder adenocarcinoma should be differentiated from urachal adenocarcinoma, which arises from urachal remnants near the bladder dome, and secondary adenocarcinoma, or vesical involvement by adenocarcinoma from a different primary. CK7, CK20, CDX2, thrombomodulin, and β-catenin can help distinguish primary bladder adenocarcinoma from colonic adenocarcinoma; PSA and PSAP can help distinguish primary bladder adenocarcinoma from prostate adenocarcinoma.